Consumer awareness and acceptance of irradiated foods: the case of Italian consumers. Issue 6 (20th June 2019) - Galati, Antonino; Moavero, Pietro; Crescimanno, Maria
Abstract : Purpose: The purpose of this paper is to investigate consumers' willingness to accept irradiated food and the major factors related both to socio-demographic characteristics and to the perceived risk of consumers about the assumption of foods treated with novel technologies and irradiation, in particular, affecting their behavior. Consumers' need for information has been investigated. Design/methodology/approach: An online survey, involving 392 consumers living in Italy, was carried out to respond to the aim of the study. A Probit model was performed in order to identify major factors affecting the probability to accept food treated with ionizing radiation. Findings: Findings show that the acceptability of irradiated foods is mainly affected by the consumers' perceived risk to health consequent to their consumption. Equally influent are the socio-economic characteristics such as age, monthly income and geographical area in which consumers live. Research limitations/implications: This study provides some interesting suggestions both for policy makers and managers, primarily related to the need to start an effective promotion campaign aimed to familiarize the consumers about the principles, aims and benefits of irradiation technology. Originality/value: Very few empirical studies have been carried out in order to evaluate the acceptability of foods products treated with ionizing radiation in Italy, where exist a growing problem related to the food loss and waste, and the need for information among consumers about the irradiated foods.